Global Oil and Gas Resources: Potential and Distribution - Dou, Lirong; Wen, Zhixin; Wang, Zhaoming; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book presents the evaluation of undiscovered oil and gas resources and reserves growth in 468 basins around the world, as well as the potential of unconventional recoverable resources of seven types, including shale oil, heavy oil, oil sands, oil shale, shale gas, coalbed methane, and tight gas. The evaluation methods used are innovative, incorporating both conventional and unconventional oil and gas resources evaluation methods that utilize plays as the fundamental evaluation unit based on various exploration maturity levels. The evaluation results obtained independent intellectual property rights and provide an overview of the future exploration potential and prospects of different regions. It is a valuable reference for researchers, practitioners, and students involved in petroleum exploration.
History and outlook of evaluation on global oil and gas resources -- Methods for evaluating global hydrocarbon resources -- Characteristics and distributions of global hydrocarbon resources -- Distribution of oil and gas resources in North America -- Distribution of oil and gas resources in Central and South America.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Geology; Cogeneration of electric power and heat; Fossil fuels; Energy policy; Energy and state; Geology; Fossil Fuel; Energy Policy, Economics and Management